A atividade principal e a velhice : contribuições da psicologia histórico-cultural - Reis, Clayton Washington dos (2011)
Along mankind history, the elderly age has been conceived and portrayed in several ways, as it takes up distinctive positions in diverse cultures and historic moments. As period of human development, the elderly age has been understood by psychology as a natural bias, whose core of explanations are based exclusively on the biopsycosocial paradigm. With the aim of building a psychology that surpass the natural vision of the human development we sought on the principles of the historical-cultural psychology, specially on the researches of L. V. Vigotski, A. N. Leontiev and D. B. Elkonin, information to understand the human development. For these authors this psychology is characterized by periods that are influenced by historical conditions of humanity. Thus, for each development period there are characteristics that are consolidated in social relations of production. This way, the periods can only be understood from the analyses of these relations. Considering the principles of the historical-cultural psychology, and having elderly age as the subject of study, we outlined as the objective of this paper to analyze the contributions that this psychological school has provided to understand the period of human development known as elderly age, considering the concept of main and dominant activity. It is important to highlight that, in this approach, the development periods are set by main or dominant activities and, they can be understood as how the individual will relate with reality, i.e., the activity which will guide the development at that moment. Based on the reflection of the theoretical principles of Historical-Cultural Psychology, a hypothesis was arisen for this study that the dominant and main activity which guides the human development during the elderly age in the capitalist society, consists of the same dominant activity which guides the adulthood, i.e., the labor activity. To accomplish this investigation about elderly age, we carried out a bibliographic research and a survey by means of semi-structured interviews with 10 elderly retirees, where 5 of them were still working in their professional activities and other 5 elderly retirees that were no longer working on any professional activity. From the collected information it was possible to understand about the elderly age from another perspective, mainly because it was sought, in the concreteness, the elements that could support and explain the existence of this period of development in the capitalist society. In this sense, we reaffirm the need of building a Psychology based on the materiality of the human existence. We could also visualize that apparently, the work has indeed guided the human development during the elderly age, as the elderly has related himself/herself with reality based on this activity. Nevertheless, the relation that the elderly establishes with his/her work finds a new meaning, considering the specificities of the moment and the material conditions that permeates his/her life.